A Study of Post Obturation Pain Following Single Visit Root Canal Treatment (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Introduction: Root canal treatment (RCT) is a common procedure in dentistry. In recent year, single visit RCT has gained increased acceptance as a treatment procedure of RCT. One of the problem of RCT is post obturation pain. Objectives: This study was conducted to determine the incidence of post obturation pain related to single visit RCT in asymptomatic non-vital single rooted teeth. Methods: A total 60 cases of endodontically involved asymptomatic non-vital single rooted teeth without any evidence of periapical radiolucency in radiograph, were selected for this study. The canals of all teeth were prepared and filled using the standarized preparation and lateral condensation filling technique. The frequency of post obturation pain was recorded as no pain, slight, moderate and severe pain and evaluated at the day l and at the day 7 after obturation. Result: Out of the 60 patients involved in the study, 37 patients had no pain, 12 patients had slight pain and 11 patients had moderate pain at the day 1 after post obturation. At the day 7 after post obturation, 50 patients had no pain, 8 patients had slight pain and 2 patients had moderate pain. No one showed severe pain in both follow up days. Conclusion: Statistically significant differences were found in the incidence and degree of pain between two follow up days. Incidence of pain was more in 1st post obturation day and decreased thereafter. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 16-19